INTERNALISASI SPIRITUALITAS ISLAM DAN MAKNA KERJA TERHADAP KINERJA KARYAWAN: STUDI KOPERASI KARYAWAN PONDOK PESANTREN ASH-SHIDDIQY, KECAMATAN LAWANG, KABUPATEN MALANG - Lina Kartikaningrum; Arien Anjar Puspitosari Suharso (ITB AAS Indonesia Surakarta, 2026)
This study aims to examine the direct and indirect influence of Islamic Spirituality Internalization and Meaning of Work on Employee Performance within the unique context of the Ash-Shiddiqy Islamic Boarding School Employee Cooperative. The research issue centers on the significance of internal, non-material dimensions as drivers of superior performance, particularly in value-based organizations. Employing a quantitative explanatory design with a positivism paradigm, the study utilized a census approach (total sampling) involving all 118 employees and teachers. Data analysis, conducted through Path Analysis, revealed that Islamic Spirituality Internalization positively and significantly affects the Meaning of Work (P=0.000) and has a significant direct influence on Employee Performance (P=0.000). Furthermore, the Meaning of Work was proven to have a positive and significant effect on Employee Performance (P=0.001). The key finding is the acceptance of the mediation hypothesis, confirming that the Meaning of Work effectively mediates the relationship between Islamic Spirituality Internalization and Employee Performance. In conclusion, the management's reinforcement of religious values (Tawhid and Amanah) can enhance Employee Performance both directly and indirectly by increasing spiritual purpose and meaning in their work, affirming the relevance of value-based HRM theories in a religious setting. Keywords: Islamic Spirituality Internalization, Meaning of Work, Employee Performance.